A scATAC-seq atlas of stasis zone in rat skin burn injury wound process - Li, Ruikang; Li, Jiashan; Liu, Shuai; Guo, Xinya; Lu, Jianyu; Wang, Tao; Chen, Junjie; Zheng, Yue; Yuan, Yue; Du, Jiaxin; Zhu, Bolin; Wei, Xiaoyu; et al. (Frontiers in Cell and Developmental Biology, 2025)
Burn injuries often leave behind a “stasis zone”, a region of tissue critically important for determining both the severity of the injury and the potential for recovery. To understand the intricate cellular and epigenetic changes occurring within this critical zone, we utilized single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to profile over 31,500 cells from both healthy rat skin and the stasis zone at nine different time points after a burn injury. This comprehensive approach revealed 26 distinct cell types and the dynamic shifts in the proportions of these cell types over time. We observed distinct gene activation patterns in different cell types at various stages post-burn, highlighting key players in immune activation, tissue regeneration, and blood vessel repair. Importantly, our analysis uncovered the regulatory networks governing these genes, offering valuable insights into the intricate mechanisms orchestrating burn wound healing. This comprehensive cellular and molecular atlas of the stasis zone provides a powerful resource for developing targeted therapies aimed at improving burn injury recovery and minimizing long-term consequences.